An upgraded CFA - FLC - MS/MS system for the semi-continuous detection of levoglucosan in ice cores - Azzurra Spagnesi; Elena Barbaro; Matteo Feltracco; Fabrizio De Blasi; Daniele Zannoni; Giuliano Dreossi; Agnese Petteni; Hanne Notø; Rachele Lodi; Jacopo Gabrieli; Rupert Holzinger; Andrea Gambaro; et al. (Talanta, 2023)
A new Continuous Flow Analysis (CFA) system coupled with Fast Liquid Chromatography – tandem Mass Spectrometry (FLC-MS/MS) has been recently developed for determining organic markers in ice cores. In this work we present an upgrade of this innovative technique, optimized for the detection of levoglucosan in ice cores, a crucial tracer for reconstructing past fires. The upgrade involved a specific optimization of the chromatographic and mass spectrometric parameters, allowing for a higher sampling resolution (down to 1 cm) and the simultaneous collection of discrete samples, for off-line analysis of water stable isotopes and additional chemical markers. The robustness and repeatability of the method has been tested by the analysis of multiple sticks of ice cut from the same shallow alpine ice core, and running the system for several hours on different days. The results show similar and comparable trends between the ice sticks. With this upgraded system, a higher sensitivity and a lower limit of detection (LOD) was achieved compared to discrete analysis of alpine samples for levoglucosan measurements. The new LOD was as low as 66 ng L−1, a net improvement over the previous LOD of 600 ng L−1.